Agriculture in developing countries technology issues - Otsuka, Keijiro.; Kalirajan, K. P. (SAGE Publications, 2008)
Technology Issues presents an experimental approach of testing new possibilities and combinations to match the changes taking place in the agricultural production environment of developing countries. While emphasizing the importance of combining scientific and indigenous knowledge, this book argues that sustained agricultural development can be achieved only by promoting farmers' participation in technology development. It provides empirical evidence for this, using recent primary data from across Asia.